INTEGRASI LITERASI INFORMASI PADA PENDIDIKAN DAN PELATIHAN JARAK JAUH PENDALAMAN MATERI BIOLOGI MADARASAH ALIYAH - Hanurani, Hikmawati (Universitas Negeri Surabaya, 2020)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This study aims to find out how the integration of information literacy substnce in distance training on biological substance for Madrasah Aliyah (MA) in improving information literacy skills in MA biology teachers. In this study the teacher participated in DistanceÂ Training on MA biological material that was integrated with information literacy substance. The research sample consisted of 26 participants in Distance TrainingÂ inÂ Biology Substance for Biology Teacher Aliyah Madrasah in the Bandung Religious Education Training Center originating from the Ministry of Religion of West Java Province. The research design used was pre-experimental design with one group pretest-posttes design. The design procedure of this study was to take the 1st measurement on the subject (pretest) on the ability of mastery of information literacy, then the subject was treated for a certain period (exposure) through education and training in e-learning based distance training deepening of Biology Substance. The second measurement (posttest) was carried out after the treatment was given, and the prestest measurement results were compared with the results of the posttest measurements, using the t-test statistical test. Based on the t-test it can be concluded that